Optimalisasi pengetahuan keluarga tentang penanganan demam pada anak di Poli Anak - Hartati, Sri; Karmi, Rudi; Hasbyalloh, Mochamad Salman; Sari, Siti Nia Purnama; Kurnia, Larisa Ardiyanti; Juniasih, Isvana Heti; Sihombing, Roasina; Amelia, Alka Fitri; Nurjanah, Wiwin; Fadilah, Gyas Syahrain (JOURNAL of Public Health Concerns, 2026)
Background: Fever is the most common complaint in children and the primary reason for visits to healthcare facilities. However, parents' lack of knowledge often leads to fever phobia, irrational medication use, and delayed recognition of danger signs. This situation emphasizes the need for systematic health education to improve family literacy. Hospitals, through pediatric clinics, play a strategic role in optimizing family knowledge, with nurses acting as educators and counselors providing evidence-based information and support. Purpose: To increase knowledge as an effort to optimize parental understanding in managing fever in children. Method: The activity was conducted in October 2025 at the Pediatric Clinic of Cibabat Regional Hospital, Cimahi, involving 25 parents selected based on their willingness and attendance. The study design used a pre-experimental, one-group pre-test and post-test, using a questionnaire on fever knowledge. Education was provided through lectures, discussions, videos, and leaflets, followed by evaluation through a post-test and Q&A. Data were analyzed descriptively by comparing pre-test and post-test results to determine improvements in family knowledge and understanding regarding fever management in children. Results: Prior to the educational activity, the knowledge and understanding of most participants were in the poor category (20 participants (82.5%) and in the adequate category (5 participants (17.5%). After the health education program, all participants improved to the good category (25 participants (100%). The comparison of the pre-test and post-test results showed a significant increase in family knowledge regarding fever management in children. Conclusion: Optimizing family knowledge about fever management in children is a crucial step in improving the quality of care and preventing complications. Appropriate and continuous education has been shown to strengthen parents' ability to manage fever independently and safely. Nurses play a strategic role as educators and counselors in providing information and support to families. Suggestion: Strengthening health education programs by nurses in healthcare facilities and the community is necessary to support fever management in children. Furthermore, the development of innovative and easily accessible educational media is expected to strengthen understanding and increase family involvement in safe and appropriate child care practices, with nurses acting as educators and counselors. Keywords: Children and toddlers; Fever; Fever management; Health education; Nursing care Pendahuluan: Demam merupakan keluhan paling sering pada anak dan menjadi alasan utama kunjungan ke fasilitas kesehatan, namun kurangnya pengetahuan orang tua sering menimbulkan fever phobia, penggunaan obat yang tidak rasional, serta keterlambatan mengenali tanda bahaya. Kondisi ini menegaskan perlunya edukasi kesehatan yang sistematis untuk meningkatkan literasi keluarga. Rumah sakit melalui poli anak memiliki peran strategis dalam optimalisasi pengetahuan keluarga, dengan perawat sebagai edukator dan konselor yang memberikan informasi berbasis bukti serta pendampingan. Tujuan: Untuk meningkatkan pengetahuan sebagai upaya optimalisasi pemahaman orang tua dalam penanganan demam pada anak. Metode: Kegiatan dilaksanakan pada Oktober 2025 di Poli Anak RSUD Cibabat Cimahi dengan melibatkan 25 orang tua yang dipilih berdasarkan kesediaan dan kehadiran. Desain penelitian menggunakan pra-eksperimental satu kelompok pre-test dan post-test dengan instrumen kuesioner pengetahuan tentang demam. Edukasi diberikan melalui ceramah, diskusi, video, dan leaflet, kemudian dilakukan evaluasi melalui post-test dan tanya-jawab. Data dianalisis secara deskriptif dengan membandingkan hasil pre-test dan post-test untuk melihat peningkatan pengetahuan dan pemahaman keluarga tentang penanganan demam pada anak. Hasil: Sebelum kegiatan edukasi, pengetahuan dan pemahaman peserta sebagian besar berada pada kategori kurang sebanyak 20 orang (82.5%) dan kategori cukup sebanyak 5 orang (17.5%). Setelah edukasi kesehatan dilaksanakan, seluruh peserta meningkat ke kategori baik yaitu 25 orang (100%). Hasil perbandingan pre-test dan post-test menunjukkan adanya peningkatan signifikan pengetahuan keluarga mengenai penanganan demam pada anak. Simpulan: Optimalisasi pengetahuan keluarga tentang penanganan demam pada anak merupakan upaya penting untuk meningkatkan kualitas perawatan dan mencegah komplikasi. Edukasi yang tepat dan berkesinambungan terbukti memperkuat kemampuan orang tua dalam menangani demam secara mandiri dan aman. Perawat memiliki peran strategis sebagai edukator dan konselor dalam memberikan informasi serta pendampingan kepada keluarga. Saran: Penguatan program edukasi kesehatan oleh perawat di fasilitas pelayanan kesehatan dan masyarakat perlu ditingkatkan untuk mendukung penanganan demam pada anak. Selain itu, pengembangan media edukasi yang inovatif dan mudah diakses diharapkan mampu memperkuat pemahaman serta meningkatkan keterlibatan keluarga dalam praktik perawatan anak yang aman dan tepat, dengan perawat berperan sebagai edukator dan konselor.